Subcapsular Renal Hematoma in Simultaneous Pancreas Kidney Transplantation - Daniele Cappellani; Chiara Terrenzio; Elena Gianetti; Walter Baronti; Valerio Borrelli; Lorella Marselli; Fabio Vistoli; Alessandro Campatelli; Ugo Boggi; Piero Marchetti (Case Reports in Transplantation)
Subcapsular renal hematoma (SRH) is a challenging condition, which may jeopardize kidney function or constitute a life-threatening event. This is particularly true in single-kidney patients, such as kidney-transplant recipients. SRH may exert an excessive pressure on the surrounding parenchyma, thus resulting in hypoperfusion and ischemia, with high risk of acute kidney failure and graft loss. Moreover, SRH may precede an overt renal rupture with subsequent hemorrhage and hemodynamic instability. The indication to an interventional management for this condition is still a matter of debate, with some authors advocating the high possibilities of spontaneous resolution and others advocating the high-risk of graft loss and even internal bleeding in case of overt renal rupture. Herein, we report the case of a 51-year-old simultaneous pancreas-kidney transplantation recipient who presented a SRH following a mild trauma. The therapeutic choices were carefully balanced on the specific case, and the conservative management proved successful.